Karakteristik Permen Keras Ekstrak Daun Jambu Biji dengan Variasi Perbandingan Sukrosa dan Sirup Glukosa - Suhardiyanto Suhardiyanto; Ngatirah Ngatirah; Herawati Oktavianty (Program Studi Teknologi Hasil Pertanian, 2023)
This research is about making hard candy from guava leaf extract and variations in the ratio of sucrose and glucose syrup which aims to determine the effect of variations in the ratio of sucrose and glucose syrup on the quality of guava leaf extract candy, determine the influence of guava leaf types on the quality of guava leaf hard candy, and obtain guava leaf types and sucrose and glucose syrup ratios that produce guava leaf candy favored by panelists and that meets the Indonesian National Standard (SNI). The research design used in this study is the Complete Block Design (RBL) with two Factor 1 Factors Sucrose Comparison: Glucose Srisup with each treatment level as follows: A1= 50:50, A2= 75:25, and A3= 85:15 and 2nd Factor – types of guava fruit parts with each level of treatment as follows: B1= Old guava leaves, B2= Young guava leaves and B3= Young guava leaves: old guava leaves (1: 1). The analysis carried out was water content, ash content, sugar reduction, antioxidant activity, phenol, Vitamin C, texture, and sensory tests (color, aroma. texture, and taste). The results of this study showed that variations in the ratio of sucrose: glucose syrup had a significant effect on the analysis of reduced sugar, vitamin C, and sensory tests of color, flavour, and Taste, but did not have a significant effect on the analysis of water content, ash content, antioxidants, phenols, texture, and sensory tests (texture). Guava leaf extract has a significant effect on the Sensory Test (Color) and has no real effect on the analysis of water content, ash content, reduction sugar, antioxidants, phenols, vitamin C, Texture, and Sensory tests (Texture, flavourma, and Taste) and variations in the ratio of sucrose with glucose syrup and the addition of guava leaf extract have a level of preference ranging from 3.86 – 4.10 where the value is also the same as Neutral so that in this manufacture the panelists have taste or the same liking for all samples